An analysis on the modern trade industry for Reckitt Benckiser (Bangladesh) PLC with concentration in damage control - Abir, Farhan Ishraq (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.